Feedyard biocontainment, biosecurity, and security risks and practices of central plains feedyards - Brandt, Aric (Kansas State University, 2007)
Biosecurity, biocontainment and security practices are important in production animal agriculture. Procuring cattle from multiple sources and commingling them into a single confinement operation increases risk of disease introduction. The large concentration of animals makes a feedyard a more likely target of a domestic or international terror group. Controlling or eradicating an intentionally introduced pathogen or toxin would be costly. The aim of these surveys was to gather information from experts about perceived risks and mitigation strategies and to assess current practices of biosecurity, biocontainment and security in Central Plains feedyards. Consulting veterinarians and feedyard managers shared similar views on the likelihood of disease caused by terrorism, natural introduction or accidental introduction, and on the importance of on-site security. They disagreed on the importance of preventative products, disease transmission control, and environmental control. Generally speaking, feedyard managers believed environmental control to be more important than consulting veterinarians. In reference to a survey of current practices, some feedyards use equipment for both manure and feed handling. Many feedyards are not cleaning and disinfecting oral treatment equipment, treatment facilities, or unloading facilities on a regular basis which may increases their risk for indirect disease transmission of endemic agents such as Salmonella or BVDV. Most feedyards in this survey import some cattle directly from an auction market, do not require clean boots or foot covering to be worn by visitors, and do not require trailers to be cleaned. Smaller feedyards were more likely to require trailers to be cleaned before loading incoming cattle. Less than half of the feedyards reported having a fence that will stop humans or kept protein supplements or micro-nutrients secured from access. Some feedyards enforced a visitor log or employed a night watchman. Most feedyards learned about a future employee by calling references listed in resume, but some performed a criminal background check. A cost-benefit analysis should be done on all management practices to determine economic benefits. More research is needed to better understand which practices are most beneficial.
Keywords: Feedyard; Biosecurity; Biocontainment; Bioterrorism; Beef; Survey; Agriculture, Animal Culture and Nutrition (0475); Biology, Veterinary Science (0778)